1975
DOI: 10.1103/physrevd.11.1477
|View full text |Cite
|
Sign up to set email alerts
|

Some nonclassical features of phase-space representations of quantum mechanics

Abstract: It is shown that phase-space distribution functions that characterize a single-particle quantum system obey a certain "generalized non-negativity condition, " which reflects the fact that the density operator is a positive operator. A corresponding criterion is obtained for the associated characteristic functions and is found to resemble, to some extent, Bochner's theorem of classical probability theory. Necessary and sufficient conditions on a phase-space representation of quantum mechanics are also derived, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Early on, these were incorrectly conjectured to be the only such mixed states with positive Wigner function. The question of mixed states was given a full treatment in [24] and latter in [25]. Both references independently found that a theorem in classical probability attributed to Bochner [26] and generalization thereof can be used to characterize both the valid Wigner functions and the subset of positive ones.…”
Section: Review Of Wigner Functionsmentioning
confidence: 99%
“…Early on, these were incorrectly conjectured to be the only such mixed states with positive Wigner function. The question of mixed states was given a full treatment in [24] and latter in [25]. Both references independently found that a theorem in classical probability attributed to Bochner [26] and generalization thereof can be used to characterize both the valid Wigner functions and the subset of positive ones.…”
Section: Review Of Wigner Functionsmentioning
confidence: 99%
“…Srinivas and Wolf [70] have proven Wigner's theorem still in a different way, yielding better insight into its physical significance. They, too, observe that operator R(q, p) in (1.165) must be a positive operator lest ρ(q, p) be positive for arbitrary density operators ρ.…”
Section: Proofmentioning
confidence: 99%
“…In order to unify the presentation, a phase space representation of both mechanics is used. Of the many equivalent quantal phase space representations (6), the Weyl correspondence (7) is used because, in this representation, the position and momentum operators are equal to their classical counterparts (8). In Sect.…”
Section: Introductionmentioning
confidence: 99%